Roots and tubers for the 21st century: trends, projections and policy options - Scott, Gregory J.; Rosegrant, Mark W.; Ringler, Claudia (International Food Policy Research Institute, 2000)
The assessment of past trends, future prospects, and policy options reported here stems from the tradition of joint studies of roots and tubers in developing countries by the Consultative Group on International Agricultural Research (CGIAR). This report builds on that previous collaboration and represents the first intercenter effort to produce future projections of demand and supply for these crops and represents the empirical foundation of a broader effort aimed at documenting not just trends and projections but also describing research activities and organizations with the overall objective of providing a vision for research on roots and tubers in the CGIAR. Gregory J. Scott, Mark W. Rosegrant, and Claudia Ringler have synthesized a significant amount of data and information on roots and tubers in order to provide a clearer vision of their past, present,a nd future roles in the food systems of developing countries. How the production and use of these commodities have changed and will continue to change over time are all the more important to understand because of the contribution they make to the diets and income-generating activities of the rural and urban poor in Asia, Africa, and Latin America. This paper provides a fuller understanding of the prospects of roots and tubers for food, feed, and other uses in developing countries in the decades ahead." (excerpted from Forward by Per Pinstrup-Andersen and Hubert Zandstra)